Clinical effect of DAPK promoter methylation in gastric cancer: A systematic meta-analysis. Issue 43 (October 2016) - Jia, Wenzhuo; Yu, Tao; Cao, Xianglong; An, Qi; Yang, Hua
Abstract: Background: The loss of death-associated protein kinase ( DAPK ) gene expression through promoter methylation is involved in many tumors. However, the relationship between DAPK promoter methylation and clinicopathological features of gastric cancer (GC) remains to be done. Therefore, we performed a meta-analysis to assess the role of DAPK promoter methylation in GC. Methods: Literature databases were searched to retrieve eligible studies. The pooled odds ratios (ORs) with its 95% confidence intervals (CIs) were calculated using the Stata 12.0 software. Results: Final 22 available studies with 1606 GC patients and 1508 nonmalignant controls were analyzed. A significant correlation was found between DAPK promoter methylation and GC (OR = 3.23, 95% CI = 1.70–6.14, P  < 0.001), but we did not find any significant association in Caucasian population, and in blood samples in subgroup analyses. DAPK promoter methylation was associated with tumor stage and lymph node status (OR = 0.69, 95% CI = 0.49–0.96, P = 0.03; OR = 1.50, 95% CI = 1.12–2.01, P = 0.007; respectively). However, we did not find that DAPK promoter methylation was associated with gender status and tumor histology. Conclusion: Our findings suggested that DAPK promoter methylation may play a key role in the carcinogenesis and progression of GC. In addition, methylated DAPK was a susceptible gene for Asian population. However, more studies with larger subjects should be done to further evaluate the effect of DAPK promoter methylation in GC patients, especially in blood and Caucasian population subgroup.